Adherence to prenatal care in the sociocultural context of developing countries: a narrative review - Dioses Fernández, Dayanna Lucia (2023)
Prenatal care is intended to preserve and improve maternal and child health; however, the quality of this service and the attendance rates vary, with developing countries having the lowest rates. There are cultural gaps that prevent adequate access to prenatal care, putting the maternal and child health at risk. Our objective was to carry out an updated review on cultural gaps and their impact on prenatal care. This narrative review was conducted by searching all articles published until December 17, 2022, in English databases such as PubMed and Scopus, and Spanish databases such as SciELO. There are various situations that force pregnant women not to attend prenatal appointment, including machismo, reported as a common cause of non-attendance to prenatal checkups in developing countries and especially in rural communities; poor education in families, so women do not attend prenatal checkups due to ignorance about pregnancy care and risks, as well as their beliefs and customs about pregnancy; difficulty accessing health care services due to geographic issues; mistreatment from health professionals while receiving prenatal care or lack of inclusion in the health center; immigration status and the resulting problems with access to health care. Recognizing these situations is as important as knowing their consequences since, once identified, different solution alternatives can be sought from the primary health care. Health personnel must be trained to help the population understand the importance of prenatal care by knowing and respecting the customs and traditions of each patient, and not undermining their ideologies.